Correction: A paper-supported sandwich immunosensor based on upconversion luminescence resonance energy transfer for the visual and quantitative determination of a cancer biomarker in human serum. Issue 15 (1st July 2020) - He, Mengyuan; Shang, Ning; Shen, Lin; Liu, Zhihong
Abstract : Correction for 'A paper-supported sandwich immunosensor based on upconversion luminescence resonance energy transfer for the visual and quantitative determination of a cancer biomarker in human serum' by Mengyuan He et al., Analyst, 2020, 145, 4181–4187, DOI: ; 10.1039/c9an02307k .